Introduction to E- learning - Aldhlan, Kawther A.; Zeki, Akram M.; Zeki, Ahmed M. (IIUM Press, 2011)
The emergence of electronic learning (e-Iearning) has further facilitated the wide adoption of learner-centered education and other changes in educational practices. Such benefits of e-Iearning are reduced education cost, consistency, timely content, flexible accessibility, and convenience. The present study provides brief description of e-Iearning, in addition, to the limitation, challenges, advantage and disadvantage of e-Iearning.